STRATEGIC PRIORITIES AND MECHANISMS OF PROTECTION OF FINANCIAL INTERESTS IN THE CONDITIONS OF SOCIAL MODERNIZATION OF THE REPUBLIC OF KAZAKHSTAN - Bakhyt Yerik Bahytula; Kaliyeva Yelena Vladimirovna; Nurpeissova Nazym Satybaldievna; Makisheva Zhanna Anatolievna; Urazbekov Abay Kargashevich (Academic Journal of Physical and Chemical Sciences, 2020)
The implementation of the financial policy should also include the growth of financial resources at the disposal of business entities, contribute to the creation of a solid financial basis for the activities of authorities for the implementation of the tasks and functions assigned to the state, to ensure the stability of social production in order to improve the economic situation of the state and social protection of the population. One of the main tasks of public finance management is to contribute to the sustainable and effective economic development of the country by optimizing budgeting. The relevance of the study of the role of the budget system in solving socio-economic problems in the Republic of Kazakhstan is determined by the fact that its functioning in the state is directly related to the realization of the socio-economic interests of society and its citizens. The budget system of Kazakhstan has a social orientation, however, it is necessary to improve the forms and methods of public administration in order to achieve efficiency and targeted use of budget funds. The article considers the main directions of social modernization of the state, analyzes the state budget expenditures on the social sphere, and directions for further stimulating the financing of social processes in Kazakhstan.